Virtual game-based learning environments to promote self-regulated learning skills in foreign language learners [version 1; peer review: 1 approved, 2 approved with reservations] - Maira Alejandra Noriega Cortes; Laura Carreño-Bolivar (F1000Research)
Background This mixed-method action research study explores the impact of a gamified virtual learning tool on elementary students’ self-regulated learning (SRL) skills in English language acquisition. Despite the acknowledged importance of SRL in educational contexts, limited research exists on its development among young learners. The present study is one of the products of the academic unit project “Key Factors and Essential Elements for a Comprehensive Model of Bilingual Education: A Multidimensional Approach for Diverse Contexts and Areas of Knowledge” sponsored by the School of Education at Universidad de La Sabana, institution where the first author conducted her master’s studies, and the corresponding author is a professor and main researcher of the of the academic unit project. Method Six students aged 8-10 participated in the study. Data were collected through semi-structured observations and pre- and post-questionnaires. The tool was designed based on Zimmerman’s SRL model and included tasks structured through gamification elements. For the purpose of quantitative data analysis, descriptive statistics were used; as for qualitative data, thematic analysis was the chosen approach. Results The results revealed that guided use of the gamified tool significantly enhanced students’ use of SRL strategies, particularly in goal setting, monitoring progress, and reflecting on learning outcomes. Students demonstrated increased motivation, engagement, and confidence, although explicit instruction was required to maximize the tool’s benefits. The usability of the tool was rated positively, with participants highlighting its effectiveness for language learning and SRL skill development. Conclusions The study concludes that gamified virtual environments can effectively promote SRL skills in young language learners by fostering motivation and engagement. However, for optimal outcomes, such tools should be supplemented with explicit instruction in SRL strategies. This research contributes to understanding the integration of gamified tools in elementary education, highlighting their potential to develop foundational skills essential for lifelong learning.